Contesting the hydrocarbon frontiers: State depoliticizing practices and local responses in Peru - Schilling-Vacaflor, Almut; Flemmer, Riccarda; Hujber, Anna (World Development, 2018)
Based on primary sources, this article analyzes 150 participatory events related to planned hydrocarbon projects in Peru (2007–2012). Therein, it sheds light on state depoliticizing practices and local populations’ contestations thereof. We argue that participation in the extraction sector has not enabled effective participation and has instead been used to pave the way for expanding the extractive frontiers. We find that the state entity responsible for carrying out the events applied three main depoliticizing practices: (a) the organization of exclusionary participatory processes, (b) the provision of pro-extraction information, and (c) the identification of critical actors and discourses in order to formulate recommendations on how to weaken resistance against the planned activities. This study also reveals that local populations often contested the participatory events and identifies subnational patterns of local contestation. We find that higher degrees of contestation were fueled by previous negative experiences with extraction activities and the existence of local economic alternatives. To assess the histories and results of contestation over specific extractive activities over time, the study draws on monthly conflict reports produced by the Peruvian ombudsperson (2007–2016). We find that local contestation was quite influential, leading to increased social investment programs in the affected areas, the withdrawal of several extraction corporations, and Peru's adoption of the Law on Prior Consultation (2011). However, the long-term prospects of the transformations provoked by repoliticizing processes need to be evaluated in the years to come.
CRIS-Team Scopus Importer:2023-11-20
Keywords: Contestation; Depoliticization; Extractive industries; Participation; Peru; Repoliticization